1984
DOI: 10.1139/z84-181
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of the gut of Sitophilus granarius (L.) (Coleoptera: Curculionidae) with notes on distribution of proteinases and amylases in crop and midgut

Abstract: In addition to typical columnar cells, dark-staining cells characterized by deep invaginations of basal plasma membranes were found throughout the midgut of adult Sitophilus granarius (L.). These invaginations formed intracellular channels that extended to the perinuclear region and indicated an involvement of these cells in secretion and (or) absorption. Cells with large vacuolelike structures that occasionally filled the entire supranuclear region were found in the anterior midgut, while multicellular crypts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…Dermestid digestion differs from that of the Coleopteran putative ancestors (Terra and Ferreira, 2005) in that most terminal digestion of carbohydrates and proteins takes place at the surface of midgut cells. These data do not confirm the earlier suggestion (Terra and Ferreira, 2005) interpret these blebs as part of the normal cell renewal process (Baker et al, 1984;Aumüller et al, 1999). Nevertheless, the presence of secretory vesicles in the blebs, which may be found in midgut lumen along with cell debris, and the signs of that of Tenebrio molitor (Cristofoletti et al, 2001).…”
Section: Distribution Of Enzyme Activities and Water Absorption Sitescontrasting
confidence: 65%
“…Dermestid digestion differs from that of the Coleopteran putative ancestors (Terra and Ferreira, 2005) in that most terminal digestion of carbohydrates and proteins takes place at the surface of midgut cells. These data do not confirm the earlier suggestion (Terra and Ferreira, 2005) interpret these blebs as part of the normal cell renewal process (Baker et al, 1984;Aumüller et al, 1999). Nevertheless, the presence of secretory vesicles in the blebs, which may be found in midgut lumen along with cell debris, and the signs of that of Tenebrio molitor (Cristofoletti et al, 2001).…”
Section: Distribution Of Enzyme Activities and Water Absorption Sitescontrasting
confidence: 65%
“…Activities toward disaccharides (sucrose, maltose and lactose) and polysaccharides (inulin and starch) were determined by the Bernfeld method (1955) as modified by Baker et al (1983). All assays were performed in triplicate.…”
Section: Carbohydrase Assaysmentioning
confidence: 99%
“…There is much research that has shown the importance and distribution of mitochondria in the midgut epithelial cells of insects (Mandel et al, 1980;Baker et al, 1984;Hung et al, 2000;Serrão and Cruz-Landim, 2000;Clark et al, 2005). It is known that the mitochondria present in the apical portion of columnar cells are involved in the absorption and metabolism of nutrients, while in the basal portion of columnar cells, this organelle is related to the nutrient and ion transport from the cell to the hemolymph (Lehane and Billingsley, 1996;Hung et al, 2000).…”
Section: Introductionmentioning
confidence: 99%